Lichens as biological indicators of air quality in the urban area of Kuršumlija (Southern Serbia) - Ristić Svetlana S.; Kosanić Marijana M.; Ranković Branislav R.; Stamenković Slaviša S. (Kragujevac Journal of Science, 2017)
In this work, we provided a first indication of Kuršumlija (town of Southern Serbia) air quality using epiphytic lichens known as bioindicators. The investigations were carried out from April to October 2014. The analysis of thalli samples (from 15 investigated points in Kuršumlija), indicates the presence of 42 lichens taxa from 23 genera. An assessment of air quality was made by using the Index of Atmospheric Purity (IAP) and Index of Human Impact (IHI). IHI values ranged between 15 and 36. IAP values ranged between 10 and 28. According to the IAP values, it has been found that there are three different air pollution zones: “normal”, “struggle” and “lichen desert”. The latest characterize the majority of the urban area. The aim of this study is to formulate an indication of air quality using lichens as bioindicators on the basis of lichens diversity and frequency. This is of great importance because there are no continuous physical and chemical measurements of air quality in this area.